Estrategia pedagógica mediada por TIC para el aprendizaje de la mecánica respiratoria, considerando situaciones problémicas y estilos de aprendizaje (2017)
Advances in knowledge and current technological developments require changes in education, redirecting it towards a student’s leading role in autonomous, meaningful and collaborative learning with thoughtful teachers and open to the search for new strategies. Medical education shares these challenges that demand critical, adaptive physicians who understand and use technological resources to solve health problems in their patients and populations.Objective. Was To design a pedagogical strategy based on problems situations and learning styles, mediated by ICT, to improve the development of competencies on respiratory mechanics.Methodology. It was designed with an experimental group and a control one, with measurements before and after in both groups. Population: Third semester medical students at a Colombian university.Results. The group that took the strategy based on problematic situations with materials adapted to the learning style and mediated by ICT, improved in comparison with the control group (p < 0.001); There was a better performance in the intervention Group (P = 0.017). The use of the pedagogical strategy did not improve the memorization of contents compared with the control (P = 0145). The satisfaction of the strategy was found in high degree.Conclusions. This strategy is a new and innovative alternative, incorporating ICT for individual and collective learning in respiratory mechanics. There should be diversity in evaluation strategies that are not limited to questionnaire-type summative assessments that do not know other evaluation processes related to meaningful learning.